FEATURES OF THE USE OF ENERGY-SAVING LIGHTING INSTALLATIONS IN ELECTRIC LIGHTING NETWORKS - Sadullaev, Aloviddin; Umirov, Asror; Bobakulov, Zavkiddin (Innovatsion texnologiyalar, 2023)
In the article, as one of the current problems of the energy system, the effective use of energy-saving lighting devices in electric lighting networks and the use of an automatic control device with a photo relay on the example of the night shift electric lighting network, the electric lighting network is continuously and the issue of quality electricity supply has been studied. Economic efficiency and energy-saving characteristics of energy-saving lamps used to ensure standard lighting in electric lighting networks are scientifically justified on the example of compact gas discharge and light-emitting diode electric lighting devices